The business of news - Droste, Heiko, 1963- (Library of the written word, 2021)
"In the seventeenth century news was an investment in social relationships, a resource that concerned the interests of members of functional elites. Exchanging news entailed different forms of participation in functional elites and, thus, privilege. This business was part of the elites' internal social structures; it constituted the fabric of all public institutions. This book questions notions of a print-based public sphere in seventeenth century. It is based on contemporary tracts on newspapers, the court culture, and letter-writers, as well as news correspondences and other archive material from archives in the Baltic Sea Region and beyond"--